Social media engagement strategy: investigation of marketing and R&D interfaces in manufacturing industry / Tasha Peter - Peter, Tasha (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
According to research, a company's new product development performance and future competitiveness are dependent on an effective marketing and R&D interface. Social media's growing popularity promised to improve engagement, collaboration, and networking between the two functions. However, little is known about the important activities, infrastructure needs, and possible benefits of social media in the marketing and research and development interface. This research intends to improve the present understanding of social media engagement techniques, allowing manufacturers to better marketing and R&D interfaces and, as a result, improve NPD performance.